Akibat Hukum Kepemilikan Senjata Tajam Tanpa Ijin - Ni Putu Ayu Sri Darma Putri; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Analogi Hukum, 2025)
Weapons that resemble sharp objects including knives, sickles, axes, machetes, etc. are referred to as sharp weapons. Considerable losses to society will arise due to the increase in crime due to the possession of sharp weapons without a license. The author examines the legal consequences for the owner of sharp weapons in the event of a criminal offense, along with the laws and regulations governing the possession of sharp weapons without a license. Normative legal research is the type of research used. The conclusion of the study shows that unlawful possession of sharp weapons can cause insignificant losses, endanger public safety and order, and disrupt community life. Sharp weapons are not always prohibited from use or possession; examples are domestic sharp weapons, agricultural weapons, heirloom weapons, and antiques. Those caught in possession of bladed weapons without a license are liable to ten months' imprisonment. To hold criminals accountable for their activities, there are penalties for those who violate criminal provisions. In this case, police officers must conduct raids with strict supervision if carrying sharp weapons without a license.